Malaysian youths at risk: a review of mental health and maladaptive behaviors - Mohamed, Shazleen; Mohamed, Shafizan; Adnan, Wardatul Hayat; Abdul Aziz, Ahlam (Zes Rokman Resources, 2022)
Young individuals who are still learning about themselves and the environment they live in are frequently at considerable risk for mental health problems due to the modern world's rapid changes and difficulties. Similar to how they were in the past, recent events have shown that Malaysian youngsters are now heavily impacted by mental health problems and are easily influenced by maladaptive habits. Maladaptive behaviours develop when people are unable to control and respond to their own emotions, stress reactions, impulses, and moods which ultimately have an impact on how they think, feel, and act. It is crucial to talk about the situation of youth mental health in Malaysia and what programmes may be implemented to support them. Youth is a significant point in a person’s life because this is the time when one starts to learn about his or her own and others' emotions. Additionally, this is a time in life when hormonal, neurological, and social changes can easily cause tension and unpleasant feelings. Thus, by describing the current state of Malaysian youth's mental health and suggesting the causes and solutions to this situation, this study attempts to emphasise the significance of discussing the state of young people's mental health. To achieve both physical and psychological well-being for the population awareness it is advisable to have screening for emotional disturbances and dysregulation for Malaysian youths in all preventive and interventional programmes. Early intervention should also be offered to prevent progression toward clinically relevant psychiatric disorders in late adolescence and adulthood.